Pengaruh Penggunaan Ekstrak Daun Katuk (Sauropus androgynus) dalam Air Minum terhadap Kecernaan Serat Kasar dan Lemak Kasar Induk Babi Bunting: The Effect of Using Extract of Katuk (Sauropus Androgynus) Leaves in Drinking Water on Crude Fiber and Crude Fat Digestability on Pregnant Sows - Oekoto, Alfret; Suryani, Ni Nengah; Sembiring, Sabarta (Jurnal Peternakan Lahan Kering, 2024)
This research aims to look at the effect of supplementation with katuk leaf solution in drinking water onconsumption, digestibility of crude fiber and crude fat of pregnant sows. The livestock used were 12 pregnantsows (second calving), with a body weight of 120-125 kg, an average of 122.5 kg and a KV of 1.46%. Acompletely randomized design with 4 groups and 3 replications was used, with the treatment T0: drinkingwater without katuk leaf solution, T1: 60 g katuk leaves in 5 ml EM-4/liter of drinking water, T2: 120 g katukleaves in 5 ml EM -4/liter of drinking water, T3: 180 g of katuk leaves in 5 ml of EM-4/liter of drinkingwater. The variables measured were consumption and digestibility of crude fiber and crude fat. The resultsshowed that katuk leaf extract 60 g, 120 g and 180 g in drinking water had no significant effect (P>0.05) onthe consumption and digestibility of crude fiber and crude fat of pregnant pigs. It was concluded thatadministration of katuk leaf extract in drinking water up to a level of 180 g/l drinking water had no effect onconsumption, and digestibility of crude fiber and crude fat of pregnant sows. Riset ini bermaksud melihat pengaruh suplementasi larutan daun katuk dalam air minum pada konsumsi,kecernaan serat kasar dan lemak kasar induk babi bunting. Ternak yang digunakan adalah 12 ekor babi induksedang bunting (beranak kedua), dengan bobot badan 120- 125 kg, rata-rata 122,5 kg dan KV 1,46%.Digunakan rancangan acak lengkap dengan 4 perlakuan dan 3 ulangan, dengan perlakuannya yaitu T0: airminum tanpa larutan daun katuk, T1: 60 g daun katuk dalam 5 ml EM-4/liter air minum, T2: 120 g daun katukdalam 5 ml EM-4/liter air minum, T3: 180 g daun katuk dalam 5 ml EM-4/liter air minum. Variabel yangdiukur yaitu konsumsi dan kecernaan serat kasar dan lemak kasar. Hasil penelitian mendapatkan ekstrakdaun katuk 60 g, 120 g dan 180 g dalam air minum memberikan pengaruh yang tidak signifikan (P>0,05)pada konsumsi dan kecernaan serat kasar dan lemak kasar babi bunting. Disimpulkan bahwa pemberianekstrak daun katuk dalam air minum sampai level 180 g/l air minum memberikan pengaruh yang sama padakonsumsi, dan kecernaan serat kasar dan lemak kasar induk babi bunting